How students learn. - Donovan, Suzanne; Bransford, John (National Academies Press, 2005)
"Organized for utility, the book explores how the principles of learning can be applied in science at three levels: elementary, middle, and high school. Leading educators explain in detail how they developed successful curricula and teaching approaches, presenting strategies that serve as models for curriculum development and classroom instruction. This book discusses how to build straightforward science experiments into true understanding of scientific principles. It also features illustrated suggestions for classroom activities."--Publisher's website.
"Division of Behavioral and Social Sciences and Education, National Research Council of the National Academies."
Includes the introduction and concluding chapter and the subset of chapters focusing on science from How students learn : history, mathematics, and science in the classroom.
Keywords: Science -- Study and teaching (Elementary); Science -- Study and teaching (Secondary); Learning.; Classroom management.; Curriculum planning.; Learning; Sciences -- Étude et enseignement (Primaire); Sciences -- Étude et enseignement (Secondaire); Apprentissage.; Classes (Éducation) -- Conduite.; EDUCATION -- Essays.; EDUCATION -- Organizations & Institutions.; EDUCATION -- Reference.; Classroom management; Curriculum planning